Short-term results of a second generation anatomic short-stem shoulder prosthesis in primary osteoarthritis - Schnetzke, Marc (Archives of orthopaedic and trauma surgery, 2019)
IntroductionThe aim of the study was to evaluate the short-term clinical results of anatomic total shoulder arthroplasty with a short-stem prosthesis in primary osteoarthritis.Materials and methods65 shoulders with a mean age of 70 years (range 47-85 years) were available for minimum follow-up of 24 months. Clinical outcome was determined by range of motion, Constant score (CS) age and sex-adjusted Constant score (CS%), and subjective shoulder value (SSV). The influence of six different factors (high bone adaptations, age > 65 years, female gender, dominant side, atrophy of the supraspinatus tendon ≥ grade 2, glenoid type B2/B3) on the clinical outcome was assessed.ResultsAt mean follow-up of 37 months (range 24-58 months), the CS improved from 36 ± 8 to 75 ± 12 (p < 0.001). The shoulder flexion (100° ± 21° to 159° ± 19°) as well as the external rotation (3° ± 11° to 43° ± 18°) improved significantly (p < 0.001). Three complications were noted (transient neuropraxia of the radial nerve, subjective instability, hematoma with superficial wound infection) leading to one revision surgery (wound debridement). No stem loosening was observed. High bone adaptation was present in 19 out of 65 shoulders (29%). The clinical outcome was not influenced by high bone adaptations (p ≥ 0.095). Age > 65 years (n = 44) and female gender (n = 38) were associated with worse clinical outcome (p ≤ 0.043).ConclusionsIn the short term, the clinical results of this anatomical short-stem shoulder prosthesis are encouraging. A low prevalence of high bone adaptations was found without any influence on the clinical outcome and stem loosening was not observed.